Regenerative Urbanism and Proximity: Designing Cities for People - Moreno, Carlos (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
The article is presented as a general overview of issue 25 of ZARCH magazine, dedicated to Regenerative Urbanism. It reviews the main theoretical contributions that make up the theoretical framework that redefines the purpose of contemporary urban planning: it is not enough to minimise urban damage, but it is necessary to regenerate life in all its dimensions—ecological, social, cultural, and spiritual—placing the city as an active agent of planetary regeneration. It reviews various areas of particular importance in this field, such as public value and the common good; the transformation of the existing city and the opportunity presented by brownfields; and urban entropy and socio-environmental rebalancing, for example. The connection between the concept of Regenerative Urbanism and the “15-minute city” approach is analysed in detail, finding clear links when it is considered that proximity cannot be achieved without prior regeneration. In conclusion, the article ends with a “Manifesto for a Proximity-Based, Just, and Culturally Vibrant City”.
Keywords: Regenerative Urban Planning; 15-Minute City; Brownfields; Urban Entropy; Topophilia